1991
DOI: 10.1017/s0265051700008032
|View full text |Cite
|
Sign up to set email alerts
|

Starting to Learn to Play a Musical Instrument: a Study of Boys' and Girls' Motivational Criteria

Abstract: The paper describes a research project undertaken recently in four primary schools. The study involved an investigation of those factors which motivated the members of a study group of 48 pupils to start learning to play a musical instrument. The findings of the research identify the importance of interest factors and the encouragement of the teacher as determinants of pupils' decisions. There is some indication of differences in the criteria used by girls and boys, particularly with regard to the socialisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
(2 reference statements)
0
10
0
2
Order By: Relevance
“…Fortney, Boyle, and DeCarbo (1993) found that 31% of students believed their music teacher influenced their choice. A similar study done in England revealed that student interest and teacher influence accounted for a summative 51 % of instrumental choice (MacKenzie, 1991 ) .…”
mentioning
confidence: 80%
“…Fortney, Boyle, and DeCarbo (1993) found that 31% of students believed their music teacher influenced their choice. A similar study done in England revealed that student interest and teacher influence accounted for a summative 51 % of instrumental choice (MacKenzie, 1991 ) .…”
mentioning
confidence: 80%
“…Likewise, and specifically with regard to musical instrument preference, there are some outstanding studies, such as that carried out by MacKenzie (1991) looking into the reasons that lead to musical instrument learning, where the student's interest and the teacher's encouragement are particularly emphasised. As regards gender differences, they are obvious, especially in relation to socialisation and its potential influence.…”
Section: Revision Of Recent Related Researchmentioning
confidence: 99%
“…Why this should be so remains an unanswered question, although it could be perceived as re ecting a societal view of music as a 'female' activity, despite the proliferation of male role models in the profession. For girls and boys, the main reason for wanting to play an instrument appears to be a personal desire to do so (MacKenzie, 1991), although social in uences appear to be more important for girls, and school factors for boys. Choice of instrument re ects stereotyping (Delzell & Leppla, 1992).…”
Section: The Characteristics Of the Individual Learnermentioning
confidence: 99%